Revisão sistemática de citogenética da família cyrenidae: inferências em população de "corbicula aff fluminea" (bivalvia: venerida) do rio Tibagi - Paraná, Brasil - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
In Evolutionary Biology, chromosomal studies, the structure and functions of genes in groups of living beings can be highlighted. Among the animal groups that have scarcity of karyotype information is the Phylum Mollusca. One of the families that is part of this group is the Cyrenidae family, which has six living genera, with 176 species. The genus Corbicula is present in different locations around the world with the presence of polyploid populations (2n = 36, 2 n = 38, 3n = 54 and 4n = 72). This genus currently has 69 species in the world. In Brazil there are four exotic representatives of this genus: Corbicula fluminea, Corbicula fluminalis, Corbicula largillierti and Corbicula sp., introduced in 1980. Therefore, the objectives of this work are: a systematic review of the state of the art of cytogenetics and ploidy of the Cyrenidae family, to carry out a qualitative analysis of this information, as well as the test of these methodologies in a population of Corbicula aff. fluminea. For this purpose, a search for digitally available articles in scientific databases (Google Academic, Scopus and Web of Science) was carried out until the year 2021. This study retrieved data from 1987 to the present and allowed us to relate karyotype information. Of the 1124 articles found, only 13 were directly related to the research topic. Regarding the karyotype characterization of the population of Corbicula aff. fluminea from the Upper Rio Tibagi, 2n = 54 chromosomes were found, in which through flow cytometry it was observed that the individuals are diploid. This work brings to light the incipient level of knowledge about the cytogenetics of this family of molluscs, some of which are invasive and with reports of poorly understood polyploidy in their origins.
Keywords: mollusca; bivalve invasor; cromossomos; ploidia; mollusca; invading bivalve; chromosomes; ploidy; CNPQ::CIENCIAS BIOLOGICAS